Ārāʾ ʿAbd al-Razzāq al-Sanhūrī wa-Taqī al-Dīn al-Nabhānī fī al-Siyāsah al-Sharʿiyyah: Dirāsah Taḥlīliyyah Muqāranah - Anas, Muhammad Khoirul; Sujoko, Imam; Syihab, Usman (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study aims to understand the concept of sharia/Islamic politics, especially according to `Abd Al-Razzāq Al-Sanhūrī and Taqī Al-Dīn Al-Nabhānī, by knowing the figures and their contributions in building the nation's civilization, and studying the points of agreement and disagreement between their opinions on the topics of Sharia politics. The study uses a descriptive analytical approach of the library research type, where the research problems are discussed by referring to the books and works of `Abd Al-Razzāq Al-Sanhūrī and Taqī Al-Dīn Al-Nabhānī, as well as other sources, from books, journals and websites related to the subject matter. Among the most important research results is that `Abd Al-Razzāq Al-Sanhūrī and Taqī Al-Dīn Al-Nabhānī agree on the need for law to establish the caliphate, the origin of the caliphate and its functions, the division of power, and the unity of the caliphate. Al-Sanhuri and al-Nabhani differed regarding the types of caliphate, and regarding the methods and procedures for establishing the caliphate.